2001
DOI: 10.1248/cpb.49.788
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Synthesis of Butyl 4-[(4-Amino-5-chloro-2-methoxybenzoyl)amino] -1-piperidineacetate (AU-224).

Abstract: We recently reported the synthesis and gastrointestinal prokinetic activity of novel benzamide derivatives with amphoteric side chains.1) Among them, 4-[(4-amino-5-chloro-2-methoxybenzoyl)amino]-1-piperidineacetic acid (1a) exhibited the most excellent gastro-and colon-prokinetic activities by intravenous administration to conscious dogs without significant dopamine D 2 receptor antagonist activity. However, 1a showed only weak gastrointestinal prokinetic activity after oral administration due to its low lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…23 Although many conditions have been reported for the solvolysis of dimethyloxazolines related to 13, this substrate proved problematic. 21,24 We found that acidic hydrolysis in ethanol was more consistently high yielding for conversion to ester 14. 25 Reduction to alcohol 15 and conversion to either bromide 16a or chloride 16b were straightforward.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…23 Although many conditions have been reported for the solvolysis of dimethyloxazolines related to 13, this substrate proved problematic. 21,24 We found that acidic hydrolysis in ethanol was more consistently high yielding for conversion to ester 14. 25 Reduction to alcohol 15 and conversion to either bromide 16a or chloride 16b were straightforward.…”
mentioning
confidence: 86%
“…Regioselective displacement of the ortho methoxy group was achieved in high yield using conditions reported by Myers 23. Although many conditions have been reported for the solvolysis of dimethyloxazolines related to 13 , this substrate proved problematic 21,24. We found that acidic hydrolysis in ethanol was more consistently high-yielding for conversion to ester 14 25.…”
mentioning
confidence: 96%
See 3 more Smart Citations